2017
DOI: 10.1007/s11060-017-2588-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of new brain metastases after radiosurgery: validation and analysis of performance of a multi-institutional nomogram

Abstract: Stereotactic radiosurgery (SRS) without whole brain radiotherapy (WBRT) for brain metastases can avoid WBRT toxicities, but with risk of subsequent distant brain failure (DBF). Sole use of number of metastases to triage patients may be an unrefined method. Data on 1354 patients treated with SRS monotherapy from 2000 to 2013 for new brain metastases was collected across eight academic centers. The cohort was divided into training and validation datasets and a prognostic model was developed for time to DBF. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
0
24
2
Order By: Relevance
“…In the cohort of Ostheimer et al, the reported median OS times for patients with multiple BM from MM were around 2.5 months despite systemic and local treatment and as short as 1.5 months with best supportive care only 29. In a recent analysis by Frinton et al, OS was 4.8 months from the diagnosis of BM and 2.2 months in patients receiving WBRT only 30. Our own previously published data had shown a median OS of 3.5 months in patients treated with WBRT and a relatively improved outcome with a higher irradiation total dose 5.…”
Section: Discussionmentioning
confidence: 98%
“…In the cohort of Ostheimer et al, the reported median OS times for patients with multiple BM from MM were around 2.5 months despite systemic and local treatment and as short as 1.5 months with best supportive care only 29. In a recent analysis by Frinton et al, OS was 4.8 months from the diagnosis of BM and 2.2 months in patients receiving WBRT only 30. Our own previously published data had shown a median OS of 3.5 months in patients treated with WBRT and a relatively improved outcome with a higher irradiation total dose 5.…”
Section: Discussionmentioning
confidence: 98%
“…An analysis by Savitz et al suggested that the cost effectiveness of using upfront SRS could be improved by concentrating the population with patients who are more likely to benefit from upfront SRS, such as those who with longer life expectancy and those with longer latency to needing salvage treatment [16]. Several statistical models have been devised to help triage patients for upfront SRS vs WBRT based on the likelihood of DBF, though the efficacy and cost-effectiveness of their use remain to be validated in a prospective setting [1719].…”
Section: Discussionmentioning
confidence: 99%
“…Cs-131 radioisotopes have been reported to have distinct radiotherapeutic advantages over I-125 isotopes including a faster half-life (9.69 days vs. 59.4 days), which may better suit an active postoperative environment and therefore be more effective [ 14 ]. Overall, the outcomes of this series are notable especially in comparison to SRS treatment, where 20–50% of brain metastases develop new or recurrent lesions within 6–12 months [ 25 - 28 ]. The median overall follow-up reported in this case series was 9.4 months, while the median time from the first craniotomy to diagnosed recurrence has been previously reported to be 6.7 months for patients with brain metastases [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%